Brucella abortus Proliferates in Decidualized and Non-Decidualized Human Endometrial Cells Inducing a Proinflammatory Response - Zavattieri, Lucia (2020)
Brucella spp. have been associated with abortion in humans and animals. Although the mechanisms involved are not well established, it is known that placental Brucella infection is accompanied by inflammatory phenomena. The ability of Brucella abortus to infect and survive in human endometrial stromal cells (T-HESC cell line) and the cytokine response elicited were evaluated. B. abortus was able to infect and proliferate in both non-decidualized and decidualized T-HESC cells. Intracellular proliferation depended on the expression of a functional virB operon in the pathogen. B. abortus internalization was inhibited by cytochalasin D and to a lower extent by colchicine, but was not affected by monodansylcadaverine. The infection did not induce cytotoxicity and did not alter the decidualization status of cells. B. abortus infection elicited the secretion of IL-8 and MCP-1 in either decidualized or non-decidualized T-HESC, a response also induced by heatkilled B. abortus and outer membrane vesicles derived from this bacterium. The stimulation of THESC with conditioned media from Brucella-infected macrophages induced the production of IL-6, MCP-1 and IL-8 in a dose-dependent manner, and this effect was shown to depend on IL-1β and TNF-α. The proinflammatory responses of T-HESC to B. abortus and to factors produced by infected macrophages may contribute to the gestational complications of brucellosis.